OPN and SPN: small molecules with great potential - Himmel, Hans-Jörg; Linti, Gerald W. (Angewandte Chemie. International edition, 2012)
Small but impressive: Since triatomic, highly reactive molecules, such as OPN, SPN (see scheme), and SiS2 have special electronic properties, they are expected to display rich and diverse reactivity. Matrix-isolation studies together with quantum chemical studies now form a solid basis for future preparative work.